Illocutionary Acts Found in Kathy Buckley’s Stand Up Comedy Videos - Listaningsih, Ni Putu Heni; Suastini, Ni Wayan; Pratiwi, Desak Putu Eka (Journal of Language and Applied Linguistics, 2023)
This research discussed about the classification of illocutionary acts found in Kathy Buckley’s Stand Up Comedy Videos. There are two problems that found in this research; first, to describe the types of illocutionary acts and second, to find out about the meaning behind the utterances. The data analysed using qualitative method. The data collected by watching some of Kathy Buckley’s stand-up comedy videos on YouTube, taking note the data that possibly contain illocutionary acts, classifying the data into types of illocutionary acts and classifying the data into types of meaning. This research used theory by Searle (1979) and theory by Leech (1981). The data source of this research was taken from Kathy Buckley Stand Up Comedy Videos found on YouTube. Moreover this research found the five types of illocutionary act, its describe as following: There are 55% data of Representative, 28% of Directive Illocutionary Acts, 3% Commissive, 11% of expressive and 3% Declarative.